Antibody titre avian influenza and Newcastle Disease in blood serum of growing ducks Gived Defferent Crude Protein Ration and vaccinated with Vaksimune NDL AI® - Purnama Edy Santosa; Rudy Sutrisna (Politeknik Negeri Lampung., 2017)
The advantages of vaccination are that it reduces the risk of infection, and concurrently reduces morbidity, mortality and shedding of virus. The goal of the present study was to evaluate efficacy of Newcastle Disease combination with Avian Influenza commercial vaccine based on humoral immunity responses of growing ducks with different feed treatments. Totally, 48 mojosari growing ducks were used in this research. The mojosari growing ducks were vaccinated using Vaksimune NDL AI®. Blood samples were collected from the axilaris vein (left or rigt) one time at postvaccination. Antibody titres were examined using Hemaglutination Inhibition (HI). The result showed that Vaksimune NDL AI® vaccine inactive ND Genotype VII strain N018 combine with AI subtype H5N1 on emultion oil was a good protection because the vaccine was able to trigger protective humoral immunity of growing ducks at 9 weeks old ducks indicated by increasing of antibody titre in blood serum of vaccinated growing ducks male during three weeks pascavaccination. Key words: Newcastle Disease, Avian influenza, vaccine, antibody, grower ducks